2013
DOI: 10.1089/acm.2012.0494
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture onYintangPoint Decreases Preoperative Anxiety

Abstract: Ear-press needle acupuncture on Yintang point reduces preoperative anxiety in adult surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Administration of acupuncture was examined during transportation and emergency cases in two studies and in nonemergency cases in eight studies; the environment in which acupuncture was administered was unclear in the remaining studies. Eight studies used acupuncture needles [10, 14, 15, 1922, 24]; the other six used acupressure balls or beads [8, 16–18, 23, 25]. Five studies applied auricular acupoints, five others applied body acupoints, and four applied both.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of acupuncture was examined during transportation and emergency cases in two studies and in nonemergency cases in eight studies; the environment in which acupuncture was administered was unclear in the remaining studies. Eight studies used acupuncture needles [10, 14, 15, 1922, 24]; the other six used acupressure balls or beads [8, 16–18, 23, 25]. Five studies applied auricular acupoints, five others applied body acupoints, and four applied both.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies also reported no significant difference in blood pressure [17, 23]. No significant changes in BIS scores were observed between groups in four studies [8, 14, 15, 18]; one of these also reported that BIS values did not differ between the groups before, during, or after acupuncture, but, during acupuncture, BIS scores were significantly lower in the group receiving acupuncture but not in the placebo group [15]. In contrast to the significant reductions seen for the primary outcome measure of anxiety, no significant difference in physiological measurements was identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture therapy aims to nourish the brain, replenish vitality, disperse liver stagnation, and smooth emotions[2324]. Previous studies[2526272829303132333435] concerning the location of acupoints in acupuncture treatment for primary depression showed that the main points are located in Du meridian, pericardium meridian, spleen meridian, liver meridian and stomach meridian; the common points are Baihui (DU20) and Yintang (EX-HN3). First, Du meridian[36] is responsible for regulating consciousness disease and organ lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Baihui [25] belongs to Du meridian and regulates mentality. Yintang [26] is responsible for nourishing the brain, replenishing vitality, and adjusting emotional disorder. Baihui and Yintang are collectively referred to as Baiyin point, which has been confirmed to be effective in the treatment of depression[2728].…”
Section: Discussionmentioning
confidence: 99%